2011
DOI: 10.1111/j.1399-3062.2011.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome in a renal transplant recipient with donor‐derived infection due to multidrug‐resistant Pseudomonas aeruginosa

Abstract: Most cases of donor-derived infection due to Pseudomonas aeruginosa reported in the literature are associated with vascular dehiscence, all of which resulted either in death or graft failure requiring graft removal. We report the successful treatment of donor-derived infection due to multidrug-resistant P. aeruginosa in a 64-year-old male who presented with bacteremia and peritransplant renal fluid collection after undergoing deceased-donor renal transplantation. As a result of the report of positive donor cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
20
0
3
Order By: Relevance
“…A thorough review of donor cultures and uniform protocols of antibiotic treatment for recipients of organs from donors infected with MDR bacteria have now been implemented at our institute. Recent reports (16)(17)(18)(19)(20) have shown that bacterial transmission can occur when posttransplant antibiotic therapy is not used in patients with postprocurement positive cultures. Ariza-Heredia et al and Goldberg et al (17,18) suggest that targeted antimicrobial treatment following transplantation can prevent transmission of MDR gram-negative pathogens, as reported for organisms with a narrower resistance profile.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…A thorough review of donor cultures and uniform protocols of antibiotic treatment for recipients of organs from donors infected with MDR bacteria have now been implemented at our institute. Recent reports (16)(17)(18)(19)(20) have shown that bacterial transmission can occur when posttransplant antibiotic therapy is not used in patients with postprocurement positive cultures. Ariza-Heredia et al and Goldberg et al (17,18) suggest that targeted antimicrobial treatment following transplantation can prevent transmission of MDR gram-negative pathogens, as reported for organisms with a narrower resistance profile.…”
Section: Casementioning
confidence: 99%
“…CRE are the source of outbreaks and can be highly lethal, with a mortality rate of 40% in SOT recipients (14). There are few reports available on the optimal evaluation and management of these highly resistant bacteria in SOT donors and recipients (15)(16)(17)(18)(19)(20). In Italy, donors with bacteremia caused by carbapenemresistant gram-negative (CRGN) bacteria are routinely excluded for any organ donation.…”
Section: Introductionmentioning
confidence: 99%
“…Mevcut çalışma nakil tipi (3)(4)(5) . Özellikle solunum yollarında gelişen pseudomonas enfeksiyonlarının innominat arter yolu ile sistemik dolaşıma geçtiği yönünde raporlar mevcuttur (6) .…”
Section: Discussionunclassified
“…Özellikle solunum yollarında gelişen pseudomonas enfeksiyonlarının innominat arter yolu ile sistemik dolaşıma geçtiği yönünde raporlar mevcuttur (6) . Nakil sonrası erken dönemde P.aeruginosa enfeksiyonunun arter anastomozunda pseudoanevrizma ve ayrışmaya neden olabileceği gösterilmiştir (3,5,7) (Tablo 1). Bu durum genellikle greft veya hasta kaybıyla sonuçla-nır.…”
Section: Discussionunclassified
See 1 more Smart Citation